The Fe(iii)-catalyzed decarboxylative cycloaddition of β-ketoacids and 2H-azirines for the synthesis of pyrrole derivatives. Issue 22 (20th October 2020) - Hu, Haipeng; Wang, Cuilin; Lai, Han; Wang, Siyuan; Ni, Hailiang; Yu, Wenhao; Cao, Peng
Abstract : An Fe(iii )-catalyzed Mannich/decarboxylative ring expansion reaction to generate pyrrole derivatives has been achieved using Fe(OTf)3 as the catalyst. A series of pyrrole derivatives was obtained in moderate to excellent yields. Abstract : An Fe(iii )-catalyzed Mannich/decarboxylative ring-expansion reaction for the synthesis of pyrrole derivatives is reported. β-Ketoacids were employed as enolate equivalents of a simple ketone and were coupled with 2 H -azirine in a formal [3 + 2] cycloaddition reaction. A series of di-, tri-alkyl/aryl-substituted and fused pyrrole derivatives was obtained in moderate to excellent yields (17–92%) under mild reaction conditions. The products could be synthesized on gram-scale with 5 mol% catalyst loading.